Production of High Protein MOCAF (Modified Cassava Flour) Using Papain and Lactic Acid Bacteria - Afifah, DIni Nur; Ma'ruf, Anwar; Putri, Regita Nanda; Santosa, Arif Prashadi; Hamad, Alwani (Molekul, 2024)
Wheat is one of Indonesia's primary sources of carbohydrates. However, the need for wheat still depends on imports. So, developing local flour based on Indonesia's natural resources is necessary. One source of carbohydrates easily found in Indonesia is cassava (Manihot esculenta crantz). Although there are many in Indonesia, the diversification of cassava-based products is still limited. In this research, MOCAF flour was developed and produced by fermenting cassava tubers with lactic acid bacteria. The enzymatic activity during the MOCAF (Modified Cassava Flour) production process is believed to change the physicochemical properties of cassava so that MOCAF products have characteristics similar to wheat flour and are expected to meet the gap between the demand and availability of flour. Even though it can potentially substitute wheat, MOCAF flour only has about 1% protein content, influencing dough rheology. According to the problem, a process modification was done by adding the enzyme papain (PAP) as a support enzyme to improve the performance of lactic acid bacteria (LAB). In order to study the effect of the papain enzyme, variations were made on the ratio of lactic acid starter: papain enzyme (LAB: PAP) and fermentation time. The ratio of (LAB: PAP) was varied to 40:1, 40:3, 40:5, 40:7, and 40:9, while the fermentation period was varied to 24, 48, 72, 96, and 120 hours. The fermentation was conducted by using cassava varieties of Singkur aerobically. The primary starter contained Lactobacillus, sp, developed by PT. Rumah Mocaf Indonesia and the papain enzyme used have an activity of 100,000 U/g. Data analysis showed that the addition of papain enzyme doses with a ratio to the lactic acid starter of 40:7 was able to produce MOCAF with the best characteristics: protein content, starch content, and swelling power of 3.72%, 9.99%, 16.00%, respectively. The data trend of research also showed that the number of papain enzymes only significantly affects starch content and swelling power. On the other hand, fermentation time has a significant effect on these three characteristics (protein, starch, swelling power).